Enhancing Undergraduate Student Skills to meet Research Challenges: Case Studies and Examples - Ransing, Rajesh (Journal of Engineering Education Transformations, 2011)
The objective of embedding research activities in the undergraduate teaching programs at State Engineering colleges in India, is worth pursuing and is certainly beneficial to all stakeholders - local industries, students and lecturers. One of the main objectives of incorporating research at an undergraduate level is to enhance student’s lateral thinking skills. We want them to develop the ability of analysing an engineering problem from first principles and recognise, as well as take into account, the work done by others, in the field. In the knowledge driven society, that is becoming truly global and interlinked, we need to equip students with an ability to challenge the status quo with independent and logical thinking. The expectation would be that students would provide solutions that offer better returns on investment for their employers. This is likely to enhance the culture of innovation in industry and increase profitability of the business. In this article, I would like to share some examples and case studies of how research can be embedded in the teaching, based on my personal experience at Swansea University (UK). My examples would range from activities that we undertake for the benefit of Swansea University undergraduate students including Government assisted programs to link student, academia and industry.